A Color Image Encryption Scheme Based on Generalized Synchronization Theorem - Han Shuangshuang; Le-Quan Min (Institute of Advanced Engineering and Science, 2014)
In order to enhance the security of image information, base on generalized synchronization theorem (GCS) for discrete chaotic system, this paper introduces a new 6-dimensional generalized chaos synchronization system based on 3D-Lorenz map. Numerical simulation showed that two pair variables of the synchronization system achieve generalized synchronization via a transform H. Combining with the 2-Dimension non equilateral Arnold transformation; a color image encryption scheme was designed. Analyzing the key sensitivity, key space, histogram, information entropy and correlation of adjacent pixels, it showed that the scheme have sound encryption and decryption effects. Numerical simulations reveal that the scheme is effective in commercial network communication for its strong anti-interference ability. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3204